Percobaan Proyek Kontinum Penulisan Artikel dan Publikasi Ilmiah Mahasiswa - Putri Anditasari; Hidayatul Fikra; Susanti Vera; Fitriani Fitriani; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2024)
This research aims to discuss the student scientific article publication continuum project experiment. This research uses a qualitative approach by applying descriptive methods. The results and discussion of the research show that the continuum trial project requires the availability of manuals, procedures and work instructions, the need for outreach to various parties ranging from stakeholders to the academic public at large, starting the implementation of the continuum project trial adequately, and not skipping the implementation of the evaluation. This research concludes that the student scientific article publication continuum project can be started immediately with experimental steps.